Assessment of Five-Year Vegetation Cover Changes to Support Green Open Spaces Monitoring in Surakarta, Central Java, Indonesia - Harahap, Moehar; Erny Poedjirahajoe,; Sigit Heru Murti Budi Santosa,; Mariah Ulfa, (Journal of Sylva Indonesiana, 2021)
Surakarta City's population is growing every year, putting pressure on the land and vegetation. Surakarta City has a population of 500,173 people in 2010. The population of this city is growing every year, driving an increase in the demand for land and living facilities. This study aims to analyze the availability of vegetated land as urban green space, and calculate the 5-year (2010“2015) vegetation cover changes. The methods used visual interpretation and on-screen digitization of the image Landsat 7 ETM+ satellite in 2010 and Landsat 8 OLI satellite image in 2015. The results show that the availability of vegetated land as urban green space in Surakarta City is lower than that mandated in Law Number 26 of 2007 concerning Spatial Planning. Vegetation cover decreased from 2010 to 2015 in Surakarta City, covering an area of 117.7 ha (2.6% of the city area) or an average of 23.5 ha (0.5%) per year. Research on the availability of green open spaces on a regular basis is expected to be part of the process of monitoring and evaluating urban development and as input for local governments in the decision-making process.